CHANGES IN THE FIELD OF MODERN EDUCATION AND FACTORS THAT IMPROVE THE QUALITY OF EDUCATION - Y. S. Xaitova (Journals Park Publishing, 2024)
In the ever-evolving landscape of the 21st century, the field of education has undergone a remarkable transformation, adapting to the dynamic needs of a rapidly changing world. As we navigate the complexities of the modern era, it has become increasingly evident that the quality of education plays a pivotal role in shaping the future of our societies. This article will delve into the significant changes that have occurred in the realm of modern education and explore the key factors that contribute to the enhancement of educational quality.
Keywords: educational reforms, government issues, educational purposes, education target, improve efficiency.